Effect of polypharmacy, potentially inappropriate medications and anticholinergic burden on clinical outcomes: a retrospective cohort study - Lu, Wan-Hsuan; Wen, Yu-Wen; Chen, Liang-Kung; Hsiao, Fei-Yuan (Canadian Medical Association journal (CMAJ), 2015)
Polypharmacy, potentially inappropriate medications and anticholinergic burden (as assessed by the anticholinergic risk scale) are commonly used as quality indicators of pharmacotherapy in older adults. However, their role in clinical practice is undefined. We sought to investigate longitudinal changes in these indicators and their effects on clinical outcomes. We used Taiwan’s Longitudinal Health Insurance Database to retrieve quarterly information about drug use for people aged 65 years and older over a 10-year period. We analyzed the association between indicators and all-cause admission to hospital, fracture-specific admission to hospital and death using generalized estimating equations. The study cohort comprised 59 042 older adults (65–74 yr: 39 358 [66.7%], 75–84 yr: 16 903 [28.6%], and ≥ 85 yr: 2781 [4.7%]). The mean changes in polypharmacy over the course of the study were greatest among patients aged 65–74 years (absolute difference +2.14, 95% confidence interval [CI] 2.10–2.19), then among those aged 75–84 yr (+1.79, 95% CI 1.70–1.88), and finally those aged 85 years and older (+0.71, 95% CI 0.36–1.05). The number of potentially inappropriate medications increased among patients aged 65–74 years (+0.16 [0.15–0.18]) and 75–84 years (+0.09 [0.06–0.08]), but decreased in those aged 85 years and older (−0.15 [−0.26 to −0.04]). Polypharmacy, potentially inappropriate medications and anticholinergic risk scale were each associated with an increased risk of admission to hospital, but not with death. In addition, both polypharmacy (5–9 drugs: odds ratio [OR] 1.18, 95% CI 1.12–1.24; ≥ 10 drugs: OR 1.54, 95% CI 1.42–1.66) and anticholinergic burden (score 1–2: 1.39, 95% CI 1.31–1.48; ≥ 3: 1.53, 95% CI 1.41–1.66) showed dose–response relations with fracture-specific admission to hospital. The total number of drugs taken (polypharmacy), number of potentially inappropriate medications and anticholinergic risk changed during follow-up and varied across age groups in this cohort of older adult patients. These indicators showed dose–response relations with admission to hospital, but not with death.